STUDENTS’ PERCEPTION OF THE USE OF GRAMMARLY IN UNDERGRADUATE THESIS WRITING - Fitria, Rina Alya; Sabarun, Sabarun; Miftah, M. Zaini (IKIP Siliwangi, 2022)
The purpose of the study was to investigate the students’ perception of using Grammarly in their undergraduate thesis writing. It also explores the Grammarly application's strengths and weaknesses. A random sampling technique was used to collect the sample. The mixed-method sequential explanatory design was used in this study. The participants of the study were 35 students enrolled in the English Education program at IAIN Palangka Raya of 2017. The SPSS 25 program was used to examine the data. The data in this study was gathered through the use of a questionnaire and an interview. The study's results showed that 80.1% of the participants highly agreed. This study found that students gave positive responses to the use of Grammarly to assist them to analyze their thesis writing. The findings showed that the Grammarly application has several strengths such as clear and easy-to-understand feedback, time savings for students when checking grammar, and a useful feature. Meanwhile, Grammarly's weaknesses are that it can’t detect tenses that the students used in a time, students can’t download the feedback in form of a file and they must pay to access all of Grammarly's premium features. Keywords: EFL Students Perception, Grammarly, Undergraduate Thesis Writing